2017
DOI: 10.5888/pcd14.160312
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cancer Screening Among Adults With Disabilities, United States, 2013

Abstract: IntroductionMany studies on cancer screening among adults with disabilities examined disability status only, which masks subgroup differences. We examined prevalence of receipt of cancer screening tests by disability status and type.MethodsWe used 2013 National Health Interview Survey data to assess prevalence of 1) guideline-concordant mammography, Papanicolaou (Pap) tests, and endoscopy and stool tests; 2) physicians’ recommendations for these tests; and 3) barriers to health-care access among adults with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 21 publications
2
63
2
1
Order By: Relevance
“…10 Cancer April 1, 2020 In many studies, women with disabilities have been shown to receive breast cancer screening at a lower rate compared with women without disabilities, [11][12][13][14][15][16][17][18] with few exeptions. 19 However, to the best of our knowledge, the majority of previous studies from the United States used cross-sectional survey data and had the following limitations: 1) use of self-report or proxy-reported disability (including disability type and severity), which is not based on objective clinical assessment; 2) use of self-report or proxy-reported breast cancer screening practices, which is subject to recall bias and fails to distinguish between tests performed for screening purposes and those tests conducted for diagnosis [11][12][13][14]16,19,20 ; and 3) inadequate sample size to yield stable participation rates across various types and severity of disabilities. 11,12,15,17,19,20 One prospective cohort study from England overcame some of the limitations of previous studies, but still involved self-reported disability status (although severity information was lacking).…”
Section: Introductionmentioning
confidence: 99%
“…10 Cancer April 1, 2020 In many studies, women with disabilities have been shown to receive breast cancer screening at a lower rate compared with women without disabilities, [11][12][13][14][15][16][17][18] with few exeptions. 19 However, to the best of our knowledge, the majority of previous studies from the United States used cross-sectional survey data and had the following limitations: 1) use of self-report or proxy-reported disability (including disability type and severity), which is not based on objective clinical assessment; 2) use of self-report or proxy-reported breast cancer screening practices, which is subject to recall bias and fails to distinguish between tests performed for screening purposes and those tests conducted for diagnosis [11][12][13][14]16,19,20 ; and 3) inadequate sample size to yield stable participation rates across various types and severity of disabilities. 11,12,15,17,19,20 One prospective cohort study from England overcame some of the limitations of previous studies, but still involved self-reported disability status (although severity information was lacking).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 72 qualified for full-text screening and 23 were considered eligible for the review. Fourteen reports provided estimates for the US (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). The other studies were conducted in Australia (one study; ref.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies provided nationally representative estimates (based on NHIS; refs. 25,32,33) and another three only included specific ethnic groups [Chinese or Chinese Americans (27), African Americans (30) and Koreans (35)].…”
Section: Resultsmentioning
confidence: 99%
“…For example, adults with disabilities are far less likely to receive important preventive screenings for cancer including mammograms and prostate checks or to have regular dental checkups. [26][27][28] Further, evidence indicates that professionals across the healthcare spectrum hold negative and stigmatizing attitudes toward PWD. 29,30 PWD also face inaccessible medical offices and examination equipment as well as office policies that prevent them from receiving adequate and accessible healthcare communications.…”
Section: Disability and Disparitiesmentioning
confidence: 99%